Either bacteriophage T4 RNase H or Escherichia coli DNA polymerase I is essential for phage replication. - Hobbs, L J (1996)
Bacteriophage T4 rnh encodes an RNase H that removes ribopentamer primers from nascent DNA chains during synthesis by the T4 multienzyme replication system in vitro (H. C. Hollingsworth and N. G. Nossal, J. Biol. Chem. 266:1888-1897, 1991). This paper demonstrates that either T4 RNase HI or Escherichia coli DNA polymerase I (Pol I) is essential for phage replication. Wild-type T4 phage production was not diminished by the polA12 mutation, which disrupts coordination between the polymerase and the 5'-to-3' nuclease activities of E. coli DNA Pol I, or by an interruption in the gene for E. coli RNase HI. Deleting the C-terminal amino acids 118 to 305 from T4 RNase H reduced phage production to 47% of that of wild-type T4 on a wild-type E. coli host, 10% on an isogenic host defective in RNase H, and less than 0.1% on a polA12 host. The T4 rnh(delta118-305) mutant synthesized DNA at about half the rate of wild-type T4 in the polA12 host. More than 50% of pulse-labelled mutant DNA was in short chains characteristic of Okazaki fragments. Phage production was restored in the nonpermissive host by providing the T4 rnh gene on a plasmid. Thus, T4 RNase H was sufficient to sustain the high rate of T4 DNA synthesis, but E. coli RNase HI and the 5'-to-3' exonuclease of Pol I could substitute to some extent for the T4 enzyme. However, replication was less accurate in the absence of the T4 RNase H, as judged by the increased frequency of acriflavine-resistant mutations after infection of a wild-type host with the T4 rnh (delta118-305) mutant.